ANALISIS PENGARUH FAKTOR MANAJERIAL, FAKTOR LINGKUNGAN, KULTUR ORGANISASI DAN PERENCANAAN STRATEGIS TERHADAP KEUNGGULAN BERSAING PT SEMEN TONASA - Arif Kurniawan; Nurdin Brasit; Indrianty Sudirman (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
The dynamics of rapidly changing business environment is one of the main factors driving the increasing competition in the market. This study aims to know to know the effect of managerial factors, the influence of environmental factors, the influence of culture / organizational culture, and strategic planning on the competitive advantage in PT Semen Tonasa. This research is included in the type of causal research that is to identify the causal relationships among variables, the researcher looks for the real type of facts to help understand and predict relationships. The result of test that has been done show that managerial factor, environmental factor, organizational culture have positive and significant influence to strategic planning, and strategic planning have positive and significant influence to company performance. Similarly, competitive advantage positively and significantly influence the company's performance.